Faktor Produksi Usahatani Padi Sawah Irigasi di Kelurahan Raya Kecamatan Turikale Kabupaten Maros - Sitti Umrah Haryamsyah; Arifin Arifin; Azisah Azisah (Universitas Muslim Maros, 2023)
Production of irrigated lowland rice is influenced by several factors, among others; seeds, fertilizers, pesticides, and labor. The purpose of this study was: To determine the factors that influence the production of rice farming in the Raya sub-district, Turikale sub-district, Maros Regency. Data were collected from field observations, direct interviews, filling out questionnaires by respondents, and other data from related agencies, namely the Maros Regency Central Statistics Agency (BPS), Agricultural Extension Center (BPP), and the Greater Village administration. The population in this study was 40 farmers. The analysis used in this study was multiple linear regression analysis to determine the factors that influence the production of irrigated lowland rice farming in Raya village, Turikale sub-district, Maros district. The results of this study can be seen, The factors that influence the production of irrigated lowland rice farming in the Raya sub-district, Turikale sub-district, and Maros district are seeds and fertilizers.